Concept Of Electronic Control Of Polarization Reconfigurable HMSIW U-Slot Antenna - Hubka, Patrik (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
This article deals with a concept of electronic control of polarization reconfigurable Uslot half-mode substrate integrated waveguide (HMSIW) antenna. Switching between left handed circular polarization (LHCP) and linear polarization (LP) is carried out by shorting the slot by two individual PIN diodes. The antenna is designed for the operating frequency of 10 GHz.
Keywords: slot antenna; half-mode substrate integrated waveguide; polarization reconfiguration